The Second Chance School – Educating and Training to Insert – Lisbon: an analysis of Socio-educational Intervention: https://doi.org/10.53809/TS_ISS_2022_n.3_52-65 ("Temas Sociais" Journal, 2022)
Currently, there are seven Second Chance Schools (E2O – Escolas de Segunda Oportunidade) in Portugal, with the first one appearing in Lisbon in 2021, where an initial study on the profile of young people and a subsequent study on the impact that this service had on them were conducted, with the purpose of analyzing the characterization of young people from the Second Chance School – Educar e Formar para Inserir – Lisbon. The use of a qualitative methodology, process analysis technique and structured interviews concluded that at the beginning of the school year, all of the 25 teenagers were unmotivated with school, 14 were already absent and 6 were dropping out at the end of the school year, most of the teens reported that this socio-educational response will be an asset for the future and that they intend to continue studying. It is worth highlighting the great contribution of the social intervention technicians who systematically monitored them and, through resilience, always adopted different strategies in order to attract these teenagers to the educational path.
Keywords: Second Chance School; Social Work; Education; School failure; School absenteeism.